Specific and common antigens of Trichomonas vaginalis detected by monoclonal antibodies. - Torian, B E (1984)
Monoclonal antibodies to Trichomonas vaginalis were prepared by immunizing mice with a cloned isolate of T. vaginalis. Eight antibodies reacted with the same four isolates or strains but did not react with the other T. vaginalis strains or isolates tested. All eight antibodies reacted uniformly with both the body and flagella of T. vaginalis in the immunofluorescence assay but were unreactive by immunoblotting. The antigen(s) recognized by these antibodies was determined to be present on the surface membrane by indirect immunofluorescence assay of live organisms. The antigen(s) was found to be sensitive to periodate oxidation but resistant to pronase digestion. In addition, one monoclonal antibody was derived which reacted with all T. vaginalis isolates or strains tested, as well as with Trichomonas gallinae, Tritrichomonas foetus, and Giardia lamblia. This antibody reacted with the body but not the flagella of Formalin-fixed protozoa in the immunofluorescence assay but failed to react with live organisms. The antigen was found to be periodate resistant but pronase labile. In the immunoblot assay, this antibody detected a single T. vaginalis polypeptide with a molecular weight of 62,000.